2005
DOI: 10.1074/jbc.m407352200
|View full text |Cite
|
Sign up to set email alerts
|

Cdk2-dependent Inhibition of p21 Stability via a C-terminal Cyclin-binding Motif

Abstract: p21 is a member of the Cip/Kip family of cyclin-dependent kinase (CDK) inhibitors that includes p21, p27, and p57. Recent studies have suggested that Cdk2 activity may promote p21 degradation through a pathway similar to that for p27, although the mechanism by which this occurs has not been clarified. In the current report, co-expression with cyclin E and Cdk2 stabilized p21 in a manner that required the CDK-binding site of p21 and a cyclin-binding site (cy1) located in the p21 N terminus. Strikingly, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 45 publications
9
47
0
1
Order By: Relevance
“…Further, disorder within the CTD of p21 (Esteve et al , 2003 ;Yoon et al , 2009 ) may mediate signal transduction from step 1 to step 2 as does that of p27 ( Figure 3A). Interestingly, it has been reported that Ser130 phosphorylation by Cdk2/cyclin E is required for ubiquitination of p21 by SCF Skp2 and its subsequent proteasomal degradation (Bornstein et al , 2003 ;Zhu et al , 2005 ). This experimental evidence supports the hypothesis that the signaling conduit observed for p27 is conserved in p21 and that NRTKs control p21 activity and stability.…”
Section: Structural Adaptation By P21 As a Mechanism Of Binding Promisupporting
confidence: 67%
See 1 more Smart Citation
“…Further, disorder within the CTD of p21 (Esteve et al , 2003 ;Yoon et al , 2009 ) may mediate signal transduction from step 1 to step 2 as does that of p27 ( Figure 3A). Interestingly, it has been reported that Ser130 phosphorylation by Cdk2/cyclin E is required for ubiquitination of p21 by SCF Skp2 and its subsequent proteasomal degradation (Bornstein et al , 2003 ;Zhu et al , 2005 ). This experimental evidence supports the hypothesis that the signaling conduit observed for p27 is conserved in p21 and that NRTKs control p21 activity and stability.…”
Section: Structural Adaptation By P21 As a Mechanism Of Binding Promisupporting
confidence: 67%
“…However, if Cdk/cyclin complexes are in excess of p21 molecules, they will additionally bind to the secondary C-terminal RxL motif. Zhu et al (2005) showed through cellular overexpression studies that this secondary interaction serves to recruit active Cdk2/cyclin E complexes for phosphorylation of p21 on Ser130. As discussed above, phosphorylation of Ser130 is a signal for p21 ubiquitination and 26S proteosomal degradation.…”
Section: Structural Adaptation By P21 As a Mechanism Of Binding Promimentioning
confidence: 99%
“…Under high-serum conditions, p21 CIP1 and p27 KIP1 are known to be unstable due to high-cyclindependent kinase activity (Morisaki et al, 1997;Zhu et al, 2005). Indeed, both p21 CIP1 and p27 KIP1 were subjected to protein degradation under high-serum conditions in the three cell types, as cycloheximide treatment resulted in reduced protein levels (Figure 4g, compare lanes 1 and 2, lanes 4 and 5 and lanes 7 and 8).…”
Section: Cell-cycle Re-entry Of G 2 -Arrested Cells Depends On Ras Anmentioning
confidence: 96%
“…Therefore, the CRL4 Cdt2 ubiquitin ligase is redundant with SCF Skp2 in promoting the destruction of p21 in S-phase cells in a similar fashion to that observed for the replication factor Cdt1. Interestingly, whereas the CRL4 Cdt2 -dependent ubiquitylation of p21 depends on p21 interaction with PCNA and is stimulated by GSK3␤-dependent phosphorylation on Ser114, SCF Skp2 -dependent ubiquitylation of p21 is promoted by p21 binding to and phosphorylation by Cdk1/2 on Ser130 (Bornstein et al 2003;Wang et al 2005;Zhu et al 2005). Thus, it is possible that CRL4 Cdt2 preferentially frees PCNA from p21, while SCF Skp2 preferentially targets p21 in complex with Cdk1/2 (see model in Fig.…”
Section: The Crl4 Cdt2 Ubiquitin Ligase Functions Redundantly With Scmentioning
confidence: 99%